Sulfate removal by fluidized bed crystallization - Rance, Diana Pearl M. (2013)
Sulfate, a common contaminant in industrial wastewaters, causes corrosion in sewers during discharge. Its possible reduction to sulfide can be a potential threat to human health. This study employed the use of crystallization process in a fluidized bed reactor to remove and recover sulfate from wastewater by continuous equal inlet dosing of sodium sulfate and calcium chloride. The effects of seed dosage, initial sulfate concentration and calcium to sulfate concentration ratio on sulfate removal and gypsum crystallization were investigated. When initial sulfate concentration was increased from 80 to 160 mM, sulfate conversion improved from 75% to 85% and removal from 55% to 78%. Sulfate crystallization followed second order kinetics indicating molecular growth. Box-Behnken Design was used to study the effects and interactions of operating parameters on sulfate conversion and removal. Optimal process conditions (Dseed = 400 g/L, [SO₄²⁻] init = 119.72 mM and [Ca²⁺]/[SO₄²⁻] = 1.48) resulted in an 81.8% sulfate conversion and 66.5% sulfate removal. Subsequent verification study was within the 95% confidence interval suggesting accuracy and adequacy of the generated models. Application of optimum parametric conditions to simulated acid mine drainage (AMD) wastewater resulted to inhibited nucleation. Product analysis crystals and silica carriers were found to be as effective as fresh gypsum seed crystals.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman
Keywords: Crystallization